2012
DOI: 10.4174/jkss.2012.82.2.63
|View full text |Cite
|
Sign up to set email alerts
|

S-plasty for pilonidal disease: modified primary closure reducing tension

Abstract: PurposeS-plasty for pilonidal disease reduces the tension on the midline by distributing it diagonally and flattening the natal cleft. The aim of this study was to evaluate the outcomes of S-plasty on simple midline primary closure and the clinical features of pilonidal patients in a low incidence country.MethodsS-plasty was applied on 17 patients from July 2008 to October 2010. Data of these patients were collected with computerized prospective database forms during a perioperative period and via telephone in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…[21] It flattens the intergluteal sulcus and diverts the incision scar from the midline. [ Figure 07] [21] S-type oblique excision Recently, the S-type oblique excision for pilonidal sinus was described, and bilateral advancement of the gluteus maximus fascia in addition to primary repair with this excision has been described as a flap reconstruction technique [27,76] . The S-type excision can be used only in lesions smaller than 3 cm with a full-thickness flap as described by Krand et al [27] .…”
Section: Excision and Primary Closure -mentioning
confidence: 99%
“…[21] It flattens the intergluteal sulcus and diverts the incision scar from the midline. [ Figure 07] [21] S-type oblique excision Recently, the S-type oblique excision for pilonidal sinus was described, and bilateral advancement of the gluteus maximus fascia in addition to primary repair with this excision has been described as a flap reconstruction technique [27,76] . The S-type excision can be used only in lesions smaller than 3 cm with a full-thickness flap as described by Krand et al [27] .…”
Section: Excision and Primary Closure -mentioning
confidence: 99%
“…In this study the incidence of recurrence was similar between the two groups [25]. The results of this study showed that recurrence is higher in patient with high VS regardless of the operation method as large volumes of tissue excised resulted in a greater recurrence rate.…”
Section: Discussionmentioning
confidence: 51%
“…Despite its higher rate of recurrence compared to marsupialization, primary closure postexcision was generally preferred because of its shorter healing time and better patient comfort [9]. Recent studies have shown that the excision used in primary closure affects the recurrence levels [10, 11]. Recurrence is affected by a deep intergluteal sulcus, the effect of vacuum developing between the buttocks, and a midline incision scar [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the S-type oblique excision for pilonidal sinus was described, and bilateral advancement of the gluteus maximus fascia in addition to primary repair with this excision has been described as a flap reconstruction technique [4, 11]. Krand et al performed tension-free repair in limited lesions using this technique and reported total complication and recurrence levels of 7.2% and 0.7%, respectively, in a series of 278 patients [4].…”
Section: Discussionmentioning
confidence: 99%